Medievalism and Exoticism in the Music of Dead Can Dance - Yri, Kirsten (Current Musicology, 2008)
In 1991, the alternative rock band Dead Can Dance released an album that caught the attention of music reviewers by constructing an aural allegiance to the Middle Ages. Suitably called A Passage in Time, the album was described as imitating medieval chant, troubadour music, Latin hymns and courtly songs and included Dead Can Dance’s hybrid medieval songs as well as performances of actual medieval repertoire. In modeling their songs and sounds after historical recordings of medieval music, Dead Can Dance also adopted some of the ideological parameters of these performances and historical reconstructions. Examining the output of Dead Can Dance against these performance practices reveals similar preoccupations with the Middle Ages as simultaneously “naive,” “pure,” and “uncorrupted” by modern conventions, or “distant,” ‘exotic,” and strangely unfamiliar or “archaic.”